Basic Norms of Integrated Systems of Management of Quality of Meat Products - Bal’-Prylypko, L.; Slobodianiuk, Nataliya Mikhailivna; Nikolayenko, Mykola Stanislavovych; Starkova, Elvina Reshativna (Wydawnictwo Uniwersytetu Rzeszowskiego, 2018)
It was shown that the optimum system of management by activities of enterprises operated in food industry, especially in producing of meat products, should be based on use of international standards requirements ISO 9001, ISO 14001, ISO 22000 and OHSAS 18001, which norms should be observed in structure of the integrated quality management system. There were analyzed the factors that influence negatively on safety of meat foods and state of nature nearby the enterprise, and proposed methods of minimization their influence. The work carried out in analysis of provisions of listed the standards permitted to choose their articles recommended for inclusion in typical structure of the integrated system of management.
Keywords: standard; safety; management; meat products; hazards; integrated quality system; development